Obóz . niezależne pismo poświęcone problemom krajów ościennych, no. 12, 1987 - Ananicz, Andrzej; Maziarski, Wojciech; Korlak, Zbigniew; Jarocińska, Sławomira (Głos Śląsko-Dąbrowski], 1987)
Creation and circulation: From issue no. 19(1990) published legally